Development of an automatic alignment conveyor system: conveyor design / Lukman Hakim Ahmad - Ahmad, Lukman Hakim (2009)
This project is to design an automatic alignment conveyor system which can contribute to decrease cycle time for repairing misaligned problem of conveyor belt. Automatic alignment conveyor system is tool to reposition the misaligned conveyor belt. This project aims at developing a simple mechanism of automatic alignment. The device is low cost and can reduce cost maintenance. The automatic alignment is operate by using pneumatic system and controlled by Programmable Logic Control (PLC) system. The developed device contains reasonable features such as easy to maintenance, simple operate and cheap. The modeling parts are built-up by using CATIA software. Parts are fabricated from the developed blue print (production drawing). Some parts are purchased directly from vendors. The fabricated and purchased parts are accordingly assembled. The assembled device is through testing process. Suitable adjustments and modifications are carried out until all requirements are met.